User Behavior Intention Towards E-Hailing Applications - Indah Wahyu Utami; Satinder Kumar; Anisha Kannu; Apif Sofyan; Fioga Zahra Fernando (Proceeding of International Conference on Science, Health, And Technology, 2021)
Technological advancements related to Global Positioning System (GPS) have led to the growth of automated transport systems. The most innovative mode of traveling is a cab/taxi which can be booked through E-hailing apps using a smartphone. The adoption of digital and information technology has brought remarkable change in the expectations and wants of the users significantly. Previous study pointed that effectiveness and usefulness help in impacting the objective to adopt m-commerce. Perceived usefulness affects user adoption of mobile securities services. As already stated, the increasing growth in the adoption of the aggregator model in India has provided profitable opportunities to unorganized taxi operators as well. Thus, the need arises to view the intention of e-hailing application usage and subsequently their effect on the users of these apps. So the objective is to Study the users’ behavior intention towards e-hailing applications.